Influencing Factors of Distance Learning Students’ Support Services in a Smart Education Environment - Zhang, ShiKe; He, ZiGuang (International Journal of Emerging Technologies in Learning (iJET), 2022)
This paper designed a questionnaire on influencing factors of distance students’ support services under the smart education environment and analyzed influences of five aspects (course support, technical support, faculty support, emotional support and management support) of students’ support services in distance education on the satisfaction of learners. Besides, differences in learners’ satisfaction in terms of gender, age groups, profession, and distance learning period were analyzed. Research results demonstrate that the Cronbach’s alpha, KMO, and p value of the designed questionnaire were 0.984, 0.855, and 0.000, respectively, indicating that that the reliability and validity of this paper are good. Course support, technical support, faculty support, and management support have statistically significant influences on learners’ satisfaction. However, emotional support does not promote learners’ satisfaction significantly. Age and distance learning period have significant differences in influencing learners’ satisfaction. Results can provide references to build a good learning support service system, promote the high-quality development of distance education and systematic construction of other types of students’ support services.